S6 peptide derived from KvAP channel shows marked differences in secondary structure after mutation- a computational approach - Chetan Malik; Rajan Shrivastava; Subhendu Ghosh; Hasan SS (International Journal of Life Sciences, 2016)
KvAP is a widely studied potassium channel from bacterium Aeropyrum pernix. It is composed of six trans-membrane domains ranging from S1 to S6. Out of these six domains, S6 is the domain through which transfer of ions occurs. We have analyzed the structural differences in the s6 domains after mutating more hydrophobic amino acids with less hydrophobic amino acids. The computational studies suggest that there is a change in the secondary structures of protein which leads to its altered functioning. The RMSD (Root mean square distance) of the peptides were calculated and significant differences were observed in Ramachandran plot. The computational analysis complements the earlier published results.